World Dictionary of Livestock Breeds - Payne, W.J.A. (Longman, 1990)
This new edition appears 30 years after the 1st edition. It is divided into three parts. The first covers basic principles, which includes effect of climate, maintenance of health, nutrition and feeding, reproduction and breeding. The second part is divided into ten chapters, discussing various animal species. The third part covers animal products. There is one appendix and an index. References are given at the end of each chapter. The importance of recording performance, the type of records required, and the need for proper breed evaluation in improvement schemes are not fully covered. This is a valuable text for all those concerned with tropical animal production.